How accurate is fine-needle aspiration cytology (FNAC) for thyroid lesion: A correlation of FNAC with histopathology - Anshu Jamaiyar; Kumar Yogesh (Journal of Family Medicine and Primary Care)
Introduction: Indian population have large number of cases with deranged thyroid profile and swelling. Clinically apparent thyroid swelling in general population is 4% to 5%. Excising all the thyroid lesions is impracticable. Thus, final-needle aspiration cytology (FNAC) serves as the initial diagnostic test for the evaluation of thyroid swelling. The main purpose of FNAC is to differentiate the benign lesion from malignant ones, thereby reducing unnecessary surgeries. This study was conducted to establish a cytohistopathological correlation. Materials and Methods: FNAC of thyroid swellings was performed using 22G or 23G needle by aspiration or nonaspiration technique, preferable nonaspiration one. A proper correlation of the history, clinical presentation, thyroid profile, and cytopathology report was made, which helped us to make a proper diagnosis. All the cases that required surgery were planned for appropriate surgery and the resected specimen of thyroid was again sent to our department for histopathological examination. Result: FNAC was performed on 39 patients (4 males and 35 females). The age group of patients were in the range of 11 to 60 years with a mean age of 38.60 years. Papillary thyroid carcinoma (PTC) and its variants were the most common in our study. Out of 39 surgeries performed, 19 (48.71%) specimens were found to be malignant. Among these 19 malignant cases, the highest number of malignancies were of PTC and its variants (14 cases). Statistical analysis showed sensitivity-90.91%, specificity-94.12%, positive predictive value-95.24%, negative predictive value-88.89%, and accuracy-92.31%. Discussion: FNAC being cost-effective, patient-friendly, quick result along with high sensitivity, specificity, and accuracy makes it an initial diagnostic tool for preoperative evaluation of patients with thyroid swelling.